A novel knockout mouse model to assess the impact of one-copy loss of Hnrnpk in CD4 + T cells in chronically inflamed skin as a prelude to CTCL - Yixin Luo; Maarten Vermeer; Margot M. Linssen; Fenna J. de Bie; Marloe Pijnacker-Verspuij; Conny Brouwers; Jill Claassens; Frank R. de Gruijl; Peter Hohenstein; Cornelis P. Tensen (Scientific Reports)
Abstract Cutaneous T-cell lymphomas (CTCLs), particularly Mycosis fungoides (MF), frequently exhibit deletions and reduced expression of HNRNPK in CD4 + T cells. To enable in vivo studies, we developed a conditional Hnrnpk knockout mouse that thrives, facilitating the investigation of HNRNPK’s role in CTCL onset. We generated mice with a floxed Hnrnpk allele, then crossbred them with Cd4CreER T 2 mice to generate Hnrnpk flox Cd4CreER T 2 mice, all in BL6 background. PCR confirmed the targeted deletion of Hnrnpk in CD4 + T cells after tamoxifen i.p. injection. Skin allergic reactions were induced with oxazolone, and Cre was activated in skin-infiltrating CD4 + T cells using tamoxifen topically after the first allergic skin reaction. The mice exhibited no immediately obvious phenotype. Flow cytometry and histopathological analysis were conducted on blood and skin samples collected throughout the experiment. Following 20 weeks of sustained allergic reactions, inflammation persisted over 20 weeks after challenges ceased, demonstrating early CTCL characteristics such as chronic skin inflammation, CD3 + CD4 + T cell infiltration, and stable peripheral blood parameters. This mouse model provides experimental access to the complex microenvironment and immune responses involved in early inflammatory stages, providing opportunities for further research into the role of HNRNPK in CTCL and the development of effective therapeutic interventions for this challenging malignancy.